Brand Switchover Behavior in Customers using Telecommunication Services - Shah Bukhari, Noor; Shaikh, Saifullah; Hussain Mirani, Sajid; Amar, Hussain; Ahmed Bhutto, Sarfaraz; Abbas Mangi, Qamar (International Journal of Psychosocial Rehabilitation, 2020)
Pakistan is considered a market that is growing in terms of customers using telecommunication services. The telecommunications market has also become competitive and has provided different alternatives to customers. Due to the competitive market, customers show brand switchover behavior. Brand switchover behavior has remained a point of concern for companies as it badly affects the concept of retaining a customer. This study identifies the factors influencing and affecting the brand switchover behavior of customers using telecommunication services in the province of Sindh. A survey was conducted from 300 respondents selected by using convenient sampling, and the data was analyzed using the factor analysis technique. Results suggest that the brand switchover behavior of customers using telecommunication services in Sindh is influenced by value-added services and pricing strategies.